2017
DOI: 10.1093/jjco/hyx052
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility to surgical robot technology and prostate-cancer patient behavior for prostatectomy

Abstract: Robotic surgery accessibility within 30 km would make patients less likely select conventional surgery. The nearer a robot was, the faster the caseload reduction was.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Patients themselves are contributing towards this trend as hospitals, and hospital systems, compete to maintain minimum procedure volumes. This process is occurring despite a lack of objective data on the quality differences in care [[33], [34], [35]]. Despite an overall shorter length of stay, robotic surgical patients had a significantly greater median hospital charge when compared to the laparoscopic or open approach.…”
Section: Discussionmentioning
confidence: 99%
“…Patients themselves are contributing towards this trend as hospitals, and hospital systems, compete to maintain minimum procedure volumes. This process is occurring despite a lack of objective data on the quality differences in care [[33], [34], [35]]. Despite an overall shorter length of stay, robotic surgical patients had a significantly greater median hospital charge when compared to the laparoscopic or open approach.…”
Section: Discussionmentioning
confidence: 99%
“…The DPC Research Institute (http://dpcri.or.jp/) has made a contract with each hospital for research use and confidentiality of the DPC data, and the data from agreed hospitals (≥80% of all DPC system participant hospitals) were accumulated as the DPC database. Approximately 1000 hospitals participated in this database in 2014 . The database includes discharge abstract and administrative claims data on acute‐care inpatients, including age; sex; main diagnosis, comorbidities at admission and complications emerging after admission coded by the International Statistical Classification of Diseases and Related Health Problems 10th Revision; and surgical procedures coded by the Japanese original codes.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 1000 hospitals participated in this database in 2014. 13 The database includes discharge abstract and administrative claims data on acute-care inpatients, including age; sex; main diagnosis, comorbidities at admission and complications emerging after admission coded by the International Statistical Classification of Diseases and Related Health Problems 10th Revision; and surgical procedures coded by the Japanese original codes.…”
Section: Data Sourcementioning
confidence: 99%
“…The accessibility to robotic surgery may also be involved in the decision making of undergoing RARP. An interesting study by Sugihara et al showed a 13% reduction in RP caseload in non-robot hospitals, whereas a 101% gain in caseload was observed in hospitals with surgical robots [ 92 ]. Another study by Muralidhar et al investigated the association between travel distance and choice of treatment [ 93 ].…”
Section: Patient Preferencementioning
confidence: 99%